Decreased glucose-6-phosphate dehydrogenase activity along with oxidative stress affects visual contrast sensitivity in alcoholics - Pramanik, Subhasish; Ganguly, Upasana; Khemka, Vineet Kumar; Banerjee, Anindita (Alcohol (Fayetteville, N.Y.), 2018)
To evaluate oxidative stress and glucose-6-phosphate dehydrogenase (G6PD) status of alcoholics and discern their association, if any, with visual contrast sensitivity function. Forty male alcoholic subjects and 36 male non-alcoholic subjects with the same age and nutritional status were enrolled in this study. Serum malondialdehyde (MDA) level and glucose-6-phosphate dehydrogenase (G6PD) activity of erythrocytes were determined by spectrophotometric assay. Contrast sensitivity (CS) function of study subjects was measured using the Rabin Contrast Sensitivity Test (Precision Vision®, La Salle, Illinois, United States). Serum MDA levels were significantly higher (p < 0.0001) and erythrocyte G6PD activity was significantly lower (p = 0.0026) in alcoholic subjects compared to the controls. CS scores of both eyes were also found to be decreased significantly in alcoholic subjects (both at p < 0.0001) compared to control subjects. On the other hand, CS scores of the alcoholic subjects were inversely correlated with the serum MDA level (r = −0.746, p < 0.0001) and directly correlated with erythrocyte G6PD activity (r = 0.78, p < 0.0001). A strong inverse correlation (r = −0.84, p < 0.0001) was also observed between serum MDA level and erythrocyte G6PD activity of alcoholic subjects. Reduced G6PD activity and increased serum MDA level might be the key cause of the early visual abnormalities, such as reduced CS function of the alcoholic subjects. •Erythrocyte G6PD activity were significantly lower and serum MDA levels were significantly higher in alcoholics compared to controls.•Visual Contrast Sensitivity score of both eyes were significantly decreased in alcoholic subjects (both at p < 0.0001) than controls.•Strong inverse correlation was observed between serum MDA and contrast sensitivity in alcoholics.•Strong positive correlation was seen between erythrocytes G6PD activity and contrast sensitivity score.•Moreover a strong inverse correlation existed between erythrocyte G6PD activity and serum MDA in alcoholics.